Cetacean sightings and acoustic detections in the offshore waters of Sri Lanka: March–June 2003 - De Vos, A.; Clark, R.; Johnson, C.; Johnson, G.; Kerr, I.; Payne, R.; Madsen, P. T. (J. Cetacean Res. Manage., 2023)
The Indian Ocean Sanctuary was established in 1979 in an effort to allow exploited stocks of whales to recover from whaling and to facilitate benign research. Further information is required to establish comprehensive management and conservation measures for species within these waters. The current study took place in the offshore waters of Sri Lanka in early 2003. During three research cruises conducted between 29 March and 17 June 2003 the R/V Odyssey covered a total track line of 4,480km around the island resulting in 52 confirmed group sightings of 11 species from three cetacean families. As the tracklines were designed to locate sperm whales (Physeter macrocephalus) for tissue sampling, they accounted for the greatest number of sightings. Only two species of balaenopterids, the blue whale (Balaenoptera musculus) and the Bryde’s whale (Balaenoptera edeni), were recorded with the blue whale being the most frequently sighted species. Spinner dolphins (Stenella longirostris) were the most dominant species in terms of numbers. Some small odonotocetes such as the common bottlenose dolphin (Tursiops truncatus), striped dolphin (Stenella coeruleoalba) and Fraser’s dolphin (Lagenodelphis hosei) were observed in mixed-species groups, while one group of melon-headed whales (Peponocephala electra) was seen associating with a group of sperm whales. Risso’s dolphins (Grampus griseus) were frequently sighted throughout the research cruise, with one unusual record of a large mating group. Many sightings were made in the vicinity of the numerous submarine canyons around Sri Lanka’s coastline highlighting their potential role in enhancing productivity in the offshore waters. It is concluded that Sri Lankan offshore waters hold a rich, but little surveyed cetacean fauna that warrants further studies and implementation of conservation measures to protect these populations.